2016
DOI: 10.1088/0963-0252/25/3/035025
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic diagnostics of low-pressure inductively coupled Kr plasma using a collisional–radiative model with fully relativistic cross sections

Abstract: A collisional-radiative (C-R) model for krypton plasma using fully relativistic distortedwave cross sections for electron excitations was developed. The model was applied to the characterization of inductively coupled Kr plasma with cylindrical geometry over the pressure regime 1-50 mTorr. Radially averaged emission intensities from transitions of Kr (4p 5 5p → 4p 5 5s) in the range 500-900 nm were recorded at 17 cm from the planar RF-driven coil, with the plasma operated in the inductive regime (H mode). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…[93] For krypton, the cross sections have been published as follows: from the ground state to the 5 s manifold, [94] to the 4 d, 5 p, and 6 s manifolds [95] and to the 6 p manifold [96] ; from the 5 s metastable levels to the 5 s and 5 p manifolds [97] ; from the 5 s manifold to the 6 p manifold. [96] These cross sections have been incorporated into a collisional-radiative model for low temperature plasmas. [93,96] Similar data for other transitions can be provided upon request.…”
Section: Ngfsrdw Databasementioning
confidence: 99%
See 2 more Smart Citations
“…[93] For krypton, the cross sections have been published as follows: from the ground state to the 5 s manifold, [94] to the 4 d, 5 p, and 6 s manifolds [95] and to the 6 p manifold [96] ; from the 5 s metastable levels to the 5 s and 5 p manifolds [97] ; from the 5 s manifold to the 6 p manifold. [96] These cross sections have been incorporated into a collisional-radiative model for low temperature plasmas. [93,96] Similar data for other transitions can be provided upon request.…”
Section: Ngfsrdw Databasementioning
confidence: 99%
“…[96] These cross sections have been incorporated into a collisional-radiative model for low temperature plasmas. [93,96] Similar data for other transitions can be provided upon request.…”
Section: Ngfsrdw Databasementioning
confidence: 99%
See 1 more Smart Citation
“…[24] In various modelling and diagnostic studies, these cross-sections were employed. [20,25] In the present work, the EIE cross-sections for neon from the ground state to the upper excited fine-structure levels and among the excited levels have been used in the model that was reported by us. [19] At low-pressure conditions, the electron energy distribution could deviate from the Maxwellian form.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear from the above discussion that most of the previous experimental or theoretical studies on Xe 7+ -Xe 10+ ions have focused on their spectroscopic properties, while the electron impact cross section data are scarcely reported. However, various studies in the past have clearly demonstrated that using accurate cross section results in a collisional radiative model provides a better agreement with the measurements on the plasma parameters, viz., electron temperature and density [17][18][19][20]. Therefore, reliable cross sections are essential for the success of any plasma model.…”
Section: Introductionmentioning
confidence: 99%